2016
DOI: 10.5194/acp-16-9891-2016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative capacity and radical chemistry in the polluted atmosphere of Hong Kong and Pearl River Delta region: analysis of a severe photochemical smog episode

Abstract: We analyze a photochemical smog episode to understand the oxidative capacity and radical chemistry of the polluted atmosphere in Hong Kong and the Pearl River Delta (PRD) region. A photochemical box model based on the Master Chemical Mechanism (MCM v3.2) is constrained by an intensive set of field observations to elucidate the budgets of RO x (RO x = OH+HO 2 +RO 2 ) and NO 3 radicals. Highly abundant radical precursors (i.e. O 3 , HONO and carbonyls), nitrogen oxides (NO x ) and volatile organic compounds (VOC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
147
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(169 citation statements)
references
References 47 publications
15
147
6
1
Order By: Relevance
“…For HO 2 , 56% to 61% of its primary production was from HCHO photolysis, with mean production rates of 1.21 and 1.06 ppb h −1 in the daytime, and 31% to 35% was from photolysis of other OVOCs with mean production rates of 0.63 and 0.66 ppb h −1 . These results are generally in line with those calculated in the polluted areas of Hong Kong (Xue et al, ) and Beijing (Liu, Wang, Gu, et al, ). In comparison, for RO 2 , the photolysis of OVOCs contributed the most (74% and 73%) during the daytime with mean production rates of 1.16 and 1.25 ppb h −1 on 23 and 24 July, respectively.…”
Section: Resultssupporting
confidence: 91%
“…For HO 2 , 56% to 61% of its primary production was from HCHO photolysis, with mean production rates of 1.21 and 1.06 ppb h −1 in the daytime, and 31% to 35% was from photolysis of other OVOCs with mean production rates of 0.63 and 0.66 ppb h −1 . These results are generally in line with those calculated in the polluted areas of Hong Kong (Xue et al, ) and Beijing (Liu, Wang, Gu, et al, ). In comparison, for RO 2 , the photolysis of OVOCs contributed the most (74% and 73%) during the daytime with mean production rates of 1.16 and 1.25 ppb h −1 on 23 and 24 July, respectively.…”
Section: Resultssupporting
confidence: 91%
“…In this study, we found that the oxidation rate of VOCs at TC (6.1 ± 2.1 × 10 6 molecules cm −3 s −1 during O 3 episodes and 5.7 ± 0.9 × 10 6 molecules cm −3 s −1 during non-episodes) was remarkably (p < 0.05) lower than that at WS (O 3 episode: 15 ± 2.5 × 10 6 molecules cm −3 s −1 and non-episode: 8.9 ± 1.3 × 10 6 molecules cm −3 s −1 ). The results revealed that the atmospheric oxidative capacity at TC was weaker than at WS for both O 3 episodes and nonepisodes, inconsistent with the findings of Elshorbany et al (2009) and Xue et al (2016), who concluded that the atmospheric oxidative capacity was higher in more polluted environments due to the fact that the atmospheric oxidative capacity is positively proportional to the VOCs and OH levels. Both Elshorbany et al (2009) andXue et al (2016) reported very high mixing ratios of VOCs (e.g., toluene of 9.5 and 6.3 ppbv, respectively) in the polluted cases, which explained the strong atmospheric oxidative capacity.…”
Section: Atmospheric Oxidative Capacity and O 3 Production Ratecontrasting
confidence: 80%
“…The results revealed that the atmospheric oxidative capacity at TC was weaker than at WS for both O 3 episodes and nonepisodes, inconsistent with the findings of Elshorbany et al (2009) and Xue et al (2016), who concluded that the atmospheric oxidative capacity was higher in more polluted environments due to the fact that the atmospheric oxidative capacity is positively proportional to the VOCs and OH levels. Both Elshorbany et al (2009) andXue et al (2016) reported very high mixing ratios of VOCs (e.g., toluene of 9.5 and 6.3 ppbv, respectively) in the polluted cases, which explained the strong atmospheric oxidative capacity. However, in this study, it is more likely that the higher NO x at TC consumed more OH and resulted in lower oxidative capacity than at WS, despite the slightly higher VOCs at TC (Table 3).…”
Section: Atmospheric Oxidative Capacity and O 3 Production Ratecontrasting
confidence: 80%
See 1 more Smart Citation
“…While the yield and speciation of the SCI formed in the ozonolysis are not well known, and depend strongly on the specific VOC, the total source strength is fairly well constrained by extensive literature data 9 where ozonolysis is known to consume a sizable fraction of the 1000 Tg of organic matter yearly emitted to the atmosphere, though its contribution is highly region-and time dependent and ranges from near-negligible to 420%. 8,[10][11][12] The main uncertainty in quantifying the ambient SCI concentration lies in the loss processes, where only simple hydrogen-and methyl-substituted SCI have been investigated in detail, [2][3][4] and only partial information exists on atmospherically more relevant SCI that are typically much larger, branched, and possibly hetero-substituted structures. The unimolecular and water reaction rate coefficients are highly dependent on the CI structure, making the analysis of CI chemistry in the atmosphere hitherto very speculative.…”
Section: Introductionmentioning
confidence: 99%